IMPROVEMENT OF THE METHODS OF TREATMENT OF TOTAL AND SUBTOTAL FORM OF EPISPADIUS AS A CAUSE OF TOTAL URINARY INCONTINENCE - Xayrulla X.Xudaynazarov (Scholar Express Journals, 2023)
Improving the methods of treatment of total and subtotal forms of epispadias as a cause of total urinary incontinence.
Keywords: Total and subtotal epispadias; total urinary incontinence